Kinship and migration in prehistoric mainland Southeast Asia: An overview of isotopic evidence. (March 2021) - Bentley, R. Alexander; Pradier, Baptiste; Kyaw, Aung Aung; Pryce, T.O.
Abstract: An exciting topic in the prehistory of Mainland Southeast Asia (MSEA) is where, when and why matriliny/matrilocality existed in certain regions during the rise of complex societies. Linguistic and genetic evidence have been used to infer kinship questions on a broad, continental scale. To contribute to this discussion on the site scale, here we summarize and compare, for the first time, almost two decades of isotopic work on prehistoric skeletons from across the region. For comparability of mobility patterns between sexes and between sites, we introduce simple normalized conversions of the (strontium, oxygen and carbon) isotopic data. Taking the evidence together, we find support for our hypothesis that matriliny/matrilocality was most likely at times and places with maritime or riverine trade, as exhibited at several coastal/deltaic sites of Thailand and Vietnam. In any case, there is an exciting future ahead for multi-method investigations into prehistoric kinship and social differentiation in Southeast Asia.